Pengontrolan Lidah Sebagai Tahap Mencapai Kekudusan Hidup - Cristian Seldjatem; Agustihana Delvryance; Otniel Otniel (Publisher STPKat, 2025)
Holiness is the key to salvation in Christianity because salvation is the main goal in Christianity, but in achieving salvation it takes holiness of life as the key for someone to be saved as written in the book of Hebrews 14: 12 that without holiness no one will see God. The writing of this article uses a descriptive qualitative approach using the literature study method which is carried out by collecting various writings, both contained in print media, theses, articles, journals, papers, and others that are relevant to the material discussed in this article. in achieving holiness, a process is needed in achieving it, so one of the steps in achieving holiness is to control the tongue because the Bible notes that who can control his tongue is perfect, the conclusion is that by practicing controlling our tongue / words every day will help us achieve holiness by keeping the tongue from being used to say things related to sin.